PENGARUH VARIASI TEKANAN DAN LAMA WAKTU PENGERINGAN HASIL PEMBRIKETAN TERHADAP KEKUATAN JATUH (DROP STRENGTH) BRIKET BIO MASSA BATUBARA - Margono Margono (JURNAL LITBANG PROVINSI JAWA TENGAH, 2007)
The effort ofdiversifying energy inthe form of classifying clean energy and its cheap, it represented by government expedient to find out ofoil and firewood for being used by smell industry and home industry. Coal is being represented 10 be an alternative energy. To reduce the environment effect delete coal burning, it is need to be mixed with biomass to make it be a bio briquette. One ofthe briquetting technique is by mixing coal and sawdust then its briquette mixture. The advantage of biocoal briquette is having combustibility much better than coal or its biomass. Mixture composition that we used are : 80% of coal: 15% of sawdust and 5% lime. The briquette form is hexagon and have a hole in its middle. The mean of this research is to exploiting biocoal to be a cheap fuel and efficient energy and used for small and hime industry,